Lessons in teaching reading comprehension in primary schools - Horton, Suzanne; Bingle, Branwen; Beattie, Louise (Los Angeles SAGE/Learning Matters, 2015)
This book provides exemplar lessons in reading for more able pupils in KS2 and uses them as a starting point for learning. It explores the theory behind good lessons, what makes them good and how they can be adapted to suit different classes and different schools.
What is reading? Reading in context Year 1: Using questioning with picture books Year 2: Developing reading comprehension through poetry Year 3: Oral storytelling and reading comprehension Year 3: Reading non-fiction Year 4: Identifying themes Year 4: Playing with plays Year 5: Using drama with a class novel Year 5: Using moving image to develop critical reading Year 6: Using drama to analyse a Shakespeare text Year 6: Analysing pre-twentieth century literature Moving on: Reading for pleasure
Keywords: Reading comprehension -- Study and teaching (Elementary).; Reading (Elementary).